A study of back-propagation and radial basis neural network on EMG signal classification - Chong, Y. L.; Sundaraj, Kenneth, Prof. Madya (Institute of Electrical and Electronics Engineering (IEEE), 2010)
Link to publisher's homepage at http://ieeexplore.ieee.org/